Cardiovascular Reactivity in Hypertensives: Differential Effect of Expressing and Inhibiting Emotions during Moments of Interpersonal Stress - Bignotto Pereira, Márcia M.; Justo, Ana Paula; Gomes de Matos, Thania M.; Lipp, Marilda E. Novaes (The Spanish Journal of Psychology, 2006)
This study investigated cardiovascular reactivity of hypertensive adults during periods of emotional stress. Two types of instructions were given at different moments, to the same subject, either to express or to suppress feelings during role play. Expressing, but not inhibiting, emotions elicited significantly higher reactivity during responding to negative scenes, followed by responding during the positive interactions. Blood pressure increases in both expressing and inhibiting conditions, were also found during the instruction periods. Results indicated that socially demanding situations represent a stressor whose effects may vary depending on whether or not respondents regulate expression of emotions. It is suggested that the difficulty in expressing emotions found in some hypertensive individuals may have the function of controlling or reducing blood pressure reactivity.